Prototype Mesin Penakar Gula Pasir Berbasir Ardiuno Uno Pada UMKM - Alfyanang Fattulah; Sayuti Rahman; Imran Lubis (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Advances in technology today have provided many benefits in various sectors, one of which is in the trade sector. Generally, traders, especially SMEs, still use conventional equipment in their activities. For example, they still use conventional scales to weigh or measure sugar, rice and so on. This activity takes a long time because traders have to reduce or add sugar if the weight is not suitable. This process often makes the weight of sugar imprecise and causes losses for traders. To overcome losses for traders, a tool is needed that can facilitate the activity of weighing the sugar. With today's very rapid technological advances, a tool can be made that can weigh sugar accurately, automatically and can be adjusted to the needs of traders. The tool uses the Arduino Uno microcontroller as the center of the system being built and also as a liaison between the sensors used. The working system is where there is a sugar storage device and automatic sugar weighing, the maximum sugar storage is 5000 grams. On the tool there are several buttons such as the 250 gram, 500 gram kg and 1000 gram buttons. When the button is pressed, the tool will remove the sugar from the storage area and weigh according to the button pressed